2010
DOI: 10.1016/j.electacta.2009.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical properties of alkali bis(trifluoromethylsulfonyl)amides and their eutectic mixtures

Abstract: Densities, viscosities and ionic conductivities of single salts and the binary eutectic mixtures of alkali bis(trifluoromethylsulfonyl)amides, MTFSAs (M = Li, Na, K, Rb, Cs), were measured in the temperature range of 413-573 K. Cyclic voltammetry revealed that the binary eutectic melts have wide electrochemical windows of 5.0-6.0 V. It was found that alkali metals reversibly deposit on a nickel electrode at the cathode limit potentials. The order of the deposition potential was determined to be Na > Li > (K, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 9 publications
4
85
0
Order By: Relevance
“…A room-temperature butylmethylpyrrolidinium-TFSI (BMP-TFSI) IL is used as the base electrolyte, since its cathodic stability limit (associated with the reduction of BMP þ ) is beyond the Na plating/stripping reaction [43] and TFSI e can withstand a high potential (>5.0 V vs. Na) [44]. Four types of Na solute, namely sodium tetrafluoroborate (NaBF 4 ), sodium perchlorate (NaClO 4 ), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), and sodium hexafluorophosphate (NaPF 6 ), are dissolved in the IL to endow it with Na þ transport ability.…”
Section: Introductionmentioning
confidence: 99%
“…A room-temperature butylmethylpyrrolidinium-TFSI (BMP-TFSI) IL is used as the base electrolyte, since its cathodic stability limit (associated with the reduction of BMP þ ) is beyond the Na plating/stripping reaction [43] and TFSI e can withstand a high potential (>5.0 V vs. Na) [44]. Four types of Na solute, namely sodium tetrafluoroborate (NaBF 4 ), sodium perchlorate (NaClO 4 ), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), and sodium hexafluorophosphate (NaPF 6 ), are dissolved in the IL to endow it with Na þ transport ability.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously investigated the thermal properties of single salts, binary and ternary mixtures of alkali metal bis(trifluoromethylsulfonyl)amides (MTFSAs; M ¼ Li, Na, K, Rb, Cs; TFSA ¼ bis(trifluoromethylsulfonyl)amide) [15,16], and alkali bis(fluorosulfonyl)amides (MFSAs; M ¼ Li, Na, K, Rb, Cs; FSA ¼ bis(fluorosulfonyl)amide) [17,18]. In the case of the TFSA salts, it was found that a Na/NaCrO 2 battery utilizing the NaTFSACsTFSA melt exhibited excellent cycle and rate performance at 423 K [19].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] From the standpoint of energy conservation, the development of a recovery process for RE metals with reduced energy consumption is desired. In previous investigations, we demonstrated the recovery of Nd metal using low-temperature molten salts (LTMSs), 8,9 because an LTMS has many useful physicochemical properties 10,11 such as a wide electrochemical window, low liquid-phase temperature, and high ionic conductivity. From an environmental point of view, LTMSs are stable compared to organic reagents and prevent the spreading of noxious decomposition chemicals because LTMSs can be recycled back into acid production cycles and be applied repeatedly as an electrolytic bath.…”
mentioning
confidence: 99%